Hak Konsumen di Tengah Ancaman: Perlindungan Hukum Terhadap Makanan dan Minuman Tidak Berlabel - Tazkia Nabila Mawarni; Ahmad Igra Ashabul Kahfi (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the legal protection for consumers against the misuse of halal labels on food and beverages traded in Parepare City, as well as understand the forms of legal protection available. Using normative and empirical research methods with a legislative approach and a conflict approach, this study combines primary and secondary data. The results of the study show that although there have been no reports of cases of misuse of the halal label in Parepare City, the local Trade Office is ready to follow up on consumer reports if any. As a preventive effort, the Trade Office is also active in providing education to the public through counselling about halal-labelled products, showing the commitment of the local government to protecting consumer rights related to halal products.